2020
DOI: 10.35784/bud-arch.2170
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the interface reinforcement on static performance of concrete composite T-shaped beams

Abstract: The tests results of composite reinforced concrete T-shaped beams with an interface between the web and the flange are presented. The interface in the beams differed in the degree of the adhesion activity and the joining reinforcement ratio. Five series of beams were tested for deflection, displacement of composite parts in relation to each other, strain of main and transverse reinforcement, and crack pattern. The results were compared with the theoretical forces, at which interface cracks and achieves the bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…For this reason, the results of tests carried out on composite beams made of concretes cast at different times are important. At this point, investigations carried out by Halicka et al can be mentioned, in which such parameters as: shape of composite beam (rectangular [15] or T-shaped [16,21]), the method of surface preparation, the intensity of the interface reinforcement, adhesion conditions (full or limited adhesion with PVC foil or release agent) [21] and location of the interface in the cross section of the composite element [16].…”
Section: Composite Beamsmentioning
confidence: 99%
“…For this reason, the results of tests carried out on composite beams made of concretes cast at different times are important. At this point, investigations carried out by Halicka et al can be mentioned, in which such parameters as: shape of composite beam (rectangular [15] or T-shaped [16,21]), the method of surface preparation, the intensity of the interface reinforcement, adhesion conditions (full or limited adhesion with PVC foil or release agent) [21] and location of the interface in the cross section of the composite element [16].…”
Section: Composite Beamsmentioning
confidence: 99%
“…concrete strength [8,[10][11][12] Type of aggregate, composition of the aggregate: ALWC (All-lightweight aggregate concrete), SLWC (Sanded-lightweight aggregate concrete), RAC (Recycled aggregate concrete) [13][14][15][16][17][18] Interface between ordinary and lightweight aggregate concrete [3,19] Shear reinforcement ratio, diameter, and location of the reinforcement [8,11,[14][15][16][20][21][22][23] Roughness of the interface [11,14,15,22,[24][25][26] Embedment depth and installation mode of the shear reinforcement [11,23] External pressure [16,24] Shape of the composite beam [27][28][29] Location of the interface within the section of the composite beam [28,29] The shear resistance of the interface is clearly related to the compressive strength of concrete, which translates into both the size of the adhesive forces and the residual load capacity in the post-peak phase (after cracking). At high shear reinforcement ratios, concrete strength determines the strength of the diagonal struts and becomes one of the parameters governing of the residual load-carrying capacity of the connection [8,15].…”
Section: Parameter Sourcementioning
confidence: 99%
“…The tests of composite beams [ 27 , 28 , 29 ] clearly show that apart from the adhesion conditions in the joint surface and the intensity of transverse reinforcement, the location of the contact at the cross-section height and the relationship between the stiffness of the base element (substrate) and the concrete overlay are important. Depending on the relation between the forces at cracking of the interface and at the shear crack formation, the failure may be initiated by cracking of the interface or proceed in the same way as in monolithic elements.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have shown a close approach to those issues, the most important being those by Halicka et al [1,14,15] and Kim et al [9,[16][17][18]. In particular, Halicka et al developed an experimental study about the influence of interface quality on the shear strength of concrete composite beams [1,14,15], in which the possible failure mechanisms in concrete composite beams are described as well as an analytical criterion to predict the failure mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental verification and comparison with existing code shear formulationsThe proposed formulation is applied to 28 specimens with web reinforcement of the experimental programme: the 9 composite rectangular specimens with B2 cross-section and ρic = ρw = 0.22%; the 10 composite T-shaped specimens with C2 and D2 cross-section and web reinforcement; the 9 monolithic T-beams with C1 and D1 cross-section and web reinforcement. Additionally, 24 shear tests from the literature are taken to study the accuracy of the proposed model in predicting the shear strength of concrete composite beams: 9 composite specimens with rectangular cross-section from Halicka[14] and 15 composite specimens with T-shaped cross-section from Jabłoński & Halicka[15]. They have similar characteristics to B2 and D2 cross-sections in this paper, respectively, but different dimensions.The results obtained are shown in Table7.…”
mentioning
confidence: 99%